Peogaruh Kualitas Layanan, Citra, Nilai dan Kepuasan terhadap Loyalitas Pasien (Studi pada Industri Rumah Sakit di Kota Makassar) - Sabri Hasan (Jurnal Aplikasi Manajemen, 2010)
Maintaning the service quality is very important for a hospital in order to assure the satisfaction and the patient loyality. Some survey resutls show that generally the system of health service in Indonesia  is not statisfactory. This is due to in capability of hospital to quarantee the quality of health service. The aims of this research are: to examine and analyze the influence of service quality of hospital towards the patient loyality. hospital image, patient value, patient satisfaction, to examine and analyze the influence of hospital image towards the loyality of patient, patient value, patient satisfaction. to Examine and analyze the influence of patient ‘s value towards the patient loyalty and patient satisfaction, the examine and analyze the influence of patient satisfaction towards the patient loyality.